2009
DOI: 10.1002/eat.20715
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and predictors of death in a cohort of patients presenting to an eating disorders service

Abstract: The study confirms previous evidence of a markedly increased mortality risk for anorexia nervosa, but also suggests that the risk is not confined to this eating disorder and that greater attention needs to be focused on wider psychiatric comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
2
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 17 publications
(18 reference statements)
1
71
2
6
Order By: Relevance
“…Thus it seemed that the systems described by the women incentivised weight loss -a finding which is worrying given that a very low BMI is a known predictor of increased mortality risk (Button, Chadalavada & Palmer, 2010). The women's narratives also suggested that even when access to a service had been achieved there was no guarantee of on-going help.…”
Section: Access To Treatmentmentioning
confidence: 99%
“…Thus it seemed that the systems described by the women incentivised weight loss -a finding which is worrying given that a very low BMI is a known predictor of increased mortality risk (Button, Chadalavada & Palmer, 2010). The women's narratives also suggested that even when access to a service had been achieved there was no guarantee of on-going help.…”
Section: Access To Treatmentmentioning
confidence: 99%
“…Mortality in AN occurs as a result of medical complications and/or suicide. Low BMI [2], older age at initial diagnosis [4], alcohol addiction, and comorbid psychiatric pathologies (e.g. depression) are considered among mortality predictors for AN.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 46% of AN patients recover completely, 30% of the patients recover partially, and 20% of the patients have a chronic disease. The risk of early mortality is 10-fold higher in AN [2]. The mortality rate in AN is higher than compared with schizophrenia, bipolar disorder, and depression [3].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite the AN prevalence rate being relatively low, ranging from 0.3% to 1% 2,3 , the functional and physiological impairments associated with this condition are pervasive. In addition, the mortality rates due to malnutrition and suicide are the highest among all psychiatric disorders [4][5][6] . Whereby, early psychosocial interventions during adolescence are associated with a positive prognostic impact, by reducing damage and preventing chronic disease [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%